Anthropocentric Ocean Connectivity: A Pluralistic Legal-Regulatory Model - Gaunce, Julia Martha; Solski, Jan Jakub; Parlov, Iva; Neves, Maria Madalena das (Arctic Review on Law and Politics, 2021)
This article proposes a model of anthropocentric ocean connectivity based on the concept of human perspective as location. Within this location, anthropocentrism can be, but is not necessarily, an exclusive or dominant valuation of the human. In fact, conceptions of both anthropocentrism and of ocean connectivity are pluralistic. These and other pluralisms are borne out in this article’s content and structure, which takes the form of explorations of anthropocentric connectivity in relation to four specific ocean-related human activities. First, Jan Solski applies understandings of connectivity as “flow” in the context of strategic ocean geopolitics. Second, Iva Parlov analyzes current doctrinal issues and interactions at the international level with respect to the legal regime for places of refuge for ships in need of assistance. Third, Maria Madalena das Neves examines ocean connectivity in the context of transboundary energy trade and market integration, with particular attention to geopolitical and ecological connectivity. Finally, Julia Gaunce proposes that the making and application of transnational rules and standards for ships in polar waters enhances certain connections and disrupts others, to the detriment of oceans and people, and that broadening connectivity especially in respect of Arctic Indigenous people(s) could help address challenges faced by oceans and ocean governance.